Good news for anxious Christians : 10 practical things you don't have to do - Cary, Phillip, 1958- (Grand Rapids, MI : Brazos Press, 2010)
"Like a succession of failed diet regimens, the much-touted techniques that are supposed to bring us closer to God 'in our hearts' can instead make us feel anxious, frustrated, and overwhelmed. How can we meet and know God with ongoing joy rather than experiencing the Christian life as a series of guilt-inducing disappointments? Drawing on his work with college students, Phillip Cary shows Christians that discipleship is a gradual, long-term process that comes through the Bible experienced in Christian community, not a to-do list designed to help them live the Christian life 'right.' This lucidly written book covers ten things Christians don't have to do to be close to God, such as hear God's voice in their hearts, find God's will for their lives, and believe their intuitions are the Holy Spirit. Presenting a time-honored approach to the gospel that is beautiful and liberating, Cary skillfully unpacks the riches of traditional Christian spirituality to bring the real good news to Christians of all ages"--Provided by publisher.
Introduction : why trying to be Christian makes us anxious -- Why you don't have to hear God's voice in your heart, or, How God really speaks today -- Why you don't have to believe your intuitions are the Holy Spirit, or, How the Spirit shapes our hearts -- Why you don't have to "let God take control," or, How obedience is for responsible adults -- Why you don't have to "find God's will for your life," or, How faith seeks wisdom -- Why you don't have to be sure you have the right motivations, or, How love seeks the good -- Why you don't have to worry about splitting head from heart, or, How thinking welcomes feeling -- Why you don't have to keep getting transformed all the time, or, How virtues make a lasting change in us -- Why you don't always have to experience joy, or, How God vindicates the afflicted -- Why "applying it to your life" is boring, or, How the gospel is beautiful -- Why basing faith on experience leads to a post-Christian future, or, How Christian faith needs Christian teaching -- Conclusion : how the gospel of Christ is good for us.
Keywords: Christian life -- Anglican authors